Relating Intimacies - Seymour, Julie. author. aut Link
XIII, 299 p.
Keywords: Relating Intimacies contains papers presented at the 1997 British Sociological Association Conference which discuss contemporary research and theorizing with regard to intimate relationships. Researchers examine the development of new forms of intimate relationships, exploring their emotional and legal dimensions, the issues of parenting in a changing world and the tensions and negotiations which are managed by those in intimate relationships. This volume will be of interest to sociologists, social policy and gender studies students, social workers and legal students.